2018
DOI: 10.3856/vol46-issue3-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary lipids concentrations on the egg production and egg quality produced by Macrobrachium acanthurus females

Abstract: ABSTRACT. The sexual maturation and reproduction of crustaceans are very demanding processes for energy and nutrients. Females require the nutrients to deposit them into the eggs and allow the healthy development of embryos and early larvae survival. The lipids are essential nutrients related to the sexual maturation and the egg production, as they are sources of metabolic energy for the gonad development, as well structural molecules for the embryonic tissue formation. This work presents the effects of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…This result does not correspond to what was observed previously in M. tenellum, where the higher densities increased their BWG , but in M. rosenbergii, it was reported that the net gain in biomass has a negative relation to stocking density (Paul et al, 2016), as seen in this study. SGR was inside the reported values for M. tenellum of about 1.3-1.5 (Ponce-Palafox et al, 2013;López-Uriostegui et al, 2014) similar to what was observed in other species such as M. acanthurus 1.1-1.4, M. amazonicum 0.65-0.90 and M. rosenbergii 0.99-1.24 (Marques et al, 2012;Banu et al, 2016;Hernández-Abad et al, 2018), suggesting that the organisms could reach the commercial weight with a longer culture time. The FCR previously reported for M. tenellum was of about 1.5-1.9 obtaining the commercial size (25 g) (García-Ulloa et al, 2008;Ponce-Palafox et al, 2013;López-Uriostegui et al, 2014), a lower FCR than the 4.335 ± 0.90 obtained in this study.…”
Section: Experimental Tank T1supporting
confidence: 86%
“…This result does not correspond to what was observed previously in M. tenellum, where the higher densities increased their BWG , but in M. rosenbergii, it was reported that the net gain in biomass has a negative relation to stocking density (Paul et al, 2016), as seen in this study. SGR was inside the reported values for M. tenellum of about 1.3-1.5 (Ponce-Palafox et al, 2013;López-Uriostegui et al, 2014) similar to what was observed in other species such as M. acanthurus 1.1-1.4, M. amazonicum 0.65-0.90 and M. rosenbergii 0.99-1.24 (Marques et al, 2012;Banu et al, 2016;Hernández-Abad et al, 2018), suggesting that the organisms could reach the commercial weight with a longer culture time. The FCR previously reported for M. tenellum was of about 1.5-1.9 obtaining the commercial size (25 g) (García-Ulloa et al, 2008;Ponce-Palafox et al, 2013;López-Uriostegui et al, 2014), a lower FCR than the 4.335 ± 0.90 obtained in this study.…”
Section: Experimental Tank T1supporting
confidence: 86%
“…This observation might also be confirmed by the contents of protein in the hepatopancreas. Although no significant differences were observed, the protein contents in the prawns' hepatopancreas fed the FOS and MOS supplemented diets were lower than those found in the control group, observed by Hernández-Abad et al (2018). According to Subramoniam (2011), proteins are mobilized from the hepatopancreas to ovaries to produce vitellogenin.…”
Section: Discussionmentioning
confidence: 87%
“…Corresponding editor: Patricio Dantagnan to Kutty & Valenti (2010) and Yamasaki-Granados et al (2012), this species' culture is an alternative to fisheries, as it might help decrease pressure on wild populations and provide employment for local fishers. Although the information on the culture conditions of M. acanthurus is still scarce (Kutty & Valenti 2010), several reports regarding their nutrient requirements are available (Hernández et al 2015, Villafuerte et al 2016, Hernández-Abad et al 2018. Prebiotics are defined as non-digestible components that are metabolized by specific health-promoting bacteria in the host's digestive system (Ringø et al 2010).…”
Section: _________________mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, HSI is high in animals fed diets with 18% lipid inclusion (Table 2). Previous studies proposed high HSI could be caused by inappropriate dietary protein/energy ratios or protein/carbohydrate levels and or excessive lipid inclusion (Hernandez‐Abad et al, 2018; Xu, Li, et al, 2017). Excessive dietary lipid negatively affects growth of juvenile P .…”
Section: Discussionmentioning
confidence: 99%